2004
DOI: 10.1038/sj.bmt.1704427
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative study of patients with total body irradiation: effects of amifostine treatment

Abstract: Summary:In patients undergoing bone marrow transplant (BMT), reactive oxygen species (ROS) are released as a consequence of the events related to the preparative regimen. Total body irradiation (TBI), which is known to generate ROS, is a routine preconditioning procedure prior to BMT. Several studies have demonstrated that amifostine protects normal tissues. In the present report, we investigated the oxidative state of plasma and erythrocytes in 21 patients with hematological malignancies undergoing TBI. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Antioxidants act as free-radical scavengers in vivo, muting the cytocidal effect of radiation in free-radical creation. There is evidence that administered antioxidants such as amifostine, 11 albana, 12 carnitine, 13 and Ginkgo biloba, 14 are radioprotective. A study on the effect of combining vitamin E and radiotherapy in mice showed a reduced radiosensitivity in the tumor cells.…”
Section: Discussionmentioning
confidence: 98%
“…Antioxidants act as free-radical scavengers in vivo, muting the cytocidal effect of radiation in free-radical creation. There is evidence that administered antioxidants such as amifostine, 11 albana, 12 carnitine, 13 and Ginkgo biloba, 14 are radioprotective. A study on the effect of combining vitamin E and radiotherapy in mice showed a reduced radiosensitivity in the tumor cells.…”
Section: Discussionmentioning
confidence: 98%
“…Schock et al [122] reported levels of antioxidant vitamins (α-tocopherol, ascorbate), urate, and protein carbonyls in bronchoalveolar lavage fluid of 83 healthy children (age range, 1.6-12.0 years). Nutritional: hyperlipidemia [42], kwashiorkor [16,111], obesity [83,103] Pharmacologic/Therapeutic: analgesics [120], anticancer drugs [117][118][119][120][121], immunosuppressive drugs [116], total body irradiation [71] Renal: glomerulonephritis [109], nephrotic syndrome [25], renal insufficiency/failure [22, 109,113], urinary tract infection [109] Respiratory: chronic pulmonary disease [115], cystic fibrosis [65,67] *The authors' works.…”
Section: Possible Oxidative Stress Involvement In Pediatric Diseasementioning
confidence: 99%
“…reported therapeutic antioxidant strategies include the following: corticosteroids for bronchial asthma [40] and bacterial meningitis [34]; L-arginine for endothelial dysfunction in cardiac transplantation [64]; angiotensinconverting enzyme inhibitors and angiotensin II type-1 receptor antagonists for endothelial dysfunction in diabetes mellitus [7,95]; melatonin for neonatal asphyxia [20] and for epilepsy [76]; folinic acid, betaine and methylcobalamin for autism [66]; tocopherols and ubiquinol/ubiquinone for Friedreich ataxia [90]; selenium for skeletal muscle disorder in selenium deficiency [59]; tocopherols and ascorbate for endothelial dysfunction in hyperlipidemia [42]; glutathione and α-lipoic acid for kwashiorkor [111]; amifostine for total body irradiation [71] and for anticancer drug use [121]; tocopherols, carotenoids and ascorbate for immunosuppressive drug use (cyclosporine A, tacrolimus) [116]; and ubiquinol/ubiquinone for anthracycline use [117].…”
Section: Endothelial Dysfunction Experimentsmentioning
confidence: 99%
“…At high doses, lipid peroxidation has been observed in irradiated model systems, including cells in vitro (3-6). In addition, increased levels of the secondary lipid peroxidation products thiobarbituric acid-reactive substances (TBARS) and 4-hydroxynonenal were reported in animal models (1, 6, 7) and in patients after total-body irradiation (TBI) (8). While peroxidation of phospholipids yields a large variety of primary and secondary oxygenated and decomposition products (9, 10), the process proceeds via the initial formation of phospholipid hydroperoxides, the most representative primary molecular peroxidation products (11).…”
Section: Introductionmentioning
confidence: 99%